Lipocalin 2 (LCN2) Expression in Hepatic Malfunction and Therapy - Asimakopoulou, Anastasia; Weiskirchen, Sabine; Weiskirchen, Ralf (Frontiers in Physiology, 2016)
Lipocalin 2 (LCN2) is a secreted protein that belongs to the Lipocalins, a group of transporters of small lipophilic molecules such as steroids, lipopolysaccharides, iron and fatty acids in circulation. Two decades after its discovery and after a high variety of published findings, LCN2’s altered expression has been assigned to critical roles in several pathological organ conditions, including liver injury and steatosis, renal damage, brain injury, cardiomyopathies, muscle-skeletal disorders, lung infection and cancer in several organs. The significance of this 25-kDa lipocalin molecule has been impressively increased during the last years. Data from several studies indicate the role of LCN2 in physiological conditions as well as in response to cellular stress and injury. LCN2 in the liver shows a protective role in acute and chronic injury models where its expression is highly elevated. Moreover, LCN2 expression is being considered as a potential strong biomarker for pathological conditions, including rheumatic diseases, cancer in human organs, hepatic steatosis, hepatic damage and inflammation. In this review, we summarize experimental and clinical findings linking LCN2 to the pathogenesis of liver disease.